View of the Neelkanth Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
This is a view of the Neelkanth Mahadev Temple seen from its southeastern corner. Also pictured here are the southern and eastern shrines of the temple as seen from the rear. The western side of the temple is its principal entrance, and the eastern shrine has a partially preserved and conserved shrine.